Neighborhood Socioeconomic Deprivation and Gender Disparities in Children with Excessive Body Weight in a Southern European Municipality - Ana C. Lourenço; Helena G. Nogueira; Daniela Rodrigues; Augusta Gama; Aristides M. Machado-Rodrigues; Maria Raquel G. Silva; Cristina Padez (Children)
Background/Objectives: Previous research has indicated that gender differences exist in the relationship between neighborhood socioeconomic (SE) deprivation and childhood excessive body weight. However, none of these studies were conducted in a metropolitan area of southern Europe. This study aims to investigate whether the association between neighborhood SE deprivation and childhood excessive body weight in the capital of the Porto Metropolitan Area is influenced by gender. Methods: The sample comprised 832 children (434 girls) aged between 3 and 10 years. Weight and height measurements were taken objectively, and body mass index (BMI) was calculated. The International Obesity Task Force cutoffs were used to identify the children with excessive body weight. Neighborhood SE deprivation was measured using the 2011 Portuguese version of the European Deprivation Index. Logistic regression models were applied for data analysis. Results: Overall, 27.8% of the participating children had excessive body weight. The prevalence of excessive body weight was higher in the neighborhoods characterized by high SE deprivation compared to those with low SE deprivation (34.4% vs. 23.1%). In a multivariable analysis, the girls living in high SE deprivation neighborhoods had a 90% higher risk of excessive body weight compared to the girls in low SE deprivation neighborhoods (OR = 1.90; 95% CI: 1.05–3.44; p = 0.035). No significant association was observed between neighborhood SE deprivation and body weight in the boys. Conclusions: The findings indicate that neighborhood SE deprivation substantially increases the risk of excessive body weight, particularly among girls. Therefore, prevention and intervention strategies aimed at addressing excessive body weight gain should specifically target the populations and areas that are at a higher risk.